Overcoming Immune Resistance With Radiation Therapy in Prostate Cancer - Mulvey, Arthur; Muggeo-Bertin, Emilien; Berthold, Dominik R.; Herrera, Fernanda G. (Frontiers in Immunology, 2022)
Prostate cancer is the second most common cancer in men and represents a significant health-care burden worldwide. Therapeutic options in the metastatic castration-resistant setting remain limited, despite advances in androgen deprivation therapy, precision medicine and targeted therapies. In this review, we summarize the role of immunotherapy in prostate cancer and offer perspectives on opportunities for future development, based on current knowledge of the immunosuppressive tumor microenvironment. Furthermore, we discuss the potential for synergistic therapeutic strategies with modern radiotherapy, through modulation of the tumor microenvironment. Emerging clinical and pre-clinical data suggests that radiation can convert immune desert tumors into an inflamed immunological hub, potentially sensitive to immunotherapy.